EXPLORING THE TEACHING AND LEARNING BELIEF OF AN INDONESIAN ENGLISH TEACHER - Hadi, Marham Jupri (JOLLT Journal of Languages and Language Teaching, 2020)
The present study investigated an English teacher?s belief regarding the best strategies to learn and teach English. A case study was employed as it explored a case (an English teacher) in depth. In-depth interviews were carried to gain deep understanding about the participant?s belief. This study reveals that he has been learning English for roughly ten years and his motivation changed from being forced to learn English (external) to having internal motivation. He believed that quality teacher affects his motivation to learn English. Concerning his personal theory about best way to learn English, he argues that there is no any best way to learn English. Instead, he believes that there are other effective approaches fitting different learning purposes. For him, the key feature to learn and teach English in his context is exposure to the language. He also believes that doing some changes like how he evaluates the learner?s skill can reduce the students? negative feeling. He admits that these preferences as the reflection of this previous learning experiences form all his experiences in learning.